TRIBOLOGICAL CHARACTERISTICS OF AVIATION LUBRICANTS UNDER CRITICAL OPERATING CONDITIONS OF TRIBOSYSTEMS - Yakobchuk, Oleksandr; Mnatsakanov, Rudolf; Popov, Dmytro; Yakobchuk, Ivan; Tsapodoi, Danil (Problems of Friction and Wear, 2026)
The article presents a comparative analysis of the tribological characteristics and wear resistance of contact surfaces under critical loads. The study uses 30KhGSA steel, extensively utilized in aviation engineering for critical components. The surfaces were lubricated with two distinct lithium-based greases: a traditional synthetic hydrocarbon-based grease (VNIINP-286M) and a modern synthetic alternative (AeroShell Grease 33). The research establishes kinetic dependencies of key parameters during simulated extreme conditions, focusing on sudden lubricant starvation. The analysis investigates the relationships between heat release intensity, friction coefficient evolution, and specific work of friction. Findings demonstrate that synthetic AeroShell Grease 33 offers superior performance for heavily loaded wing high-lift devices. This synthetic grease forms and maintains highly stable boundary lubricating films under extreme stress, providing higher resistance to thermal and oxidative degradation. Consequently, it drastically reduces the probability of localized overheating, severe scuffing, and adhesive wear compared to traditional synthetic counterparts, highlighting the importance of advanced synthetic lubricants for modern aviation machinery.